The Correlations of Advertising Exposure and Communication Competency of Sales Marketing with Buying Interest of Toyota All New Sienta - Christanti, Rhenita; Herieningsih, MS, Dra. Sri Widowati (Interaksi Online, 2017)
Car is high involvement product for some people. Altough not a primary needs, can not lie if car is must-have thing for now. Appearance of LCGC (Low Cost Green Car) cars in Indonesia, doesn‟t make car brand Toyota loses hope to bring a new car in MPV (Multi Purpose Vehicle) class. All New Sienta, is a brand new car that launch in 2016, July. As a new product with complete features and modern design, All New Sienta considered to be the „new rising star‟ amon others car in the same class. But in fact, people seems not interest with All New Sienta.The purpose of this research is to know the correlations of advertising exposure and communication competency of sales marketing with buying interest of Toyota All New Sienta. This is a explanatory research and use Advertising Exposure Process Theory for measure advertising exposure and Speech Act Theory for measure communication competency. The sample of respondent of this research were the sample of 60 respondents who are lived in Semarang, have regular pay and family, which are fitted with market segmentation of All New Sienta.The result of hypothesis test used Kendall‟s Tau-b, that correlation between advertising exposure with buying interest in significant score 0,001 (<0,05) and correlation coefficient score is 0,337 that means this correlations is in the average class of correlation, and then the correlation between communication competency with buying interest in significant score 0,000 (<0,05) and correlation coefficient score is 0,557 which are include in strong correlation class.Based on research result, can be deduced that; 1) there is a positive correlation between advertising exposure with buying interest of Toyota All New Sienta; 2) there is a positive correlation between communication competency with buying interest of Toyota All New Sienta. The research shows that advertising and communication skills of sales marketing are effective promotion tools for increase buying interest of All New Sienta. Toyota is expected to continue to innovate in advertising and advertising media to be able to reach the target consumers appropriately.